Penetration of Cefamandole, Cephalothin, and Desacetylcephalothin into Fibrin Clots - Bergeron, Michel G. (1977)
The conversion of cephalothin into a less active metabolite (desacetylcephalothin) might influence its distribution in tissues. An experimental rabbit model devised to determine concentrations of antibiotics in subcutaneous fibrin clots was used in this study. Groups of five to six animals received 100-mg/kg intravenous injections of either cefamandole or cephalothin. One hour after the injection, the concentration of cefamandole in serum was 20 times higher than that of cephalothin. Whereas cephalothin was undetectable at 4 h, cefamandole was still detectable at the end of the experiment. The half-lives of cephalothin and cefamandole in serum were 16 and 27 min, respectively. The concentration of cefamandole found in fibrin clots was severalfold higher than that of cephalothin. The half-life of cefamandole in clots (81 min) was superior to that of cephalothin (38 min). Although concentrations of both antibiotics were higher in serum than in clots at 1 h, the concentrations of these drugs in the clots persisted at higher levels throughout the next 5 h of the experiment. The extent of binding of cefamandole (87%) to rabbit serum was greater than that of cephalothin (50%). At least 55% of cephalothin was metabolized in vivo into its less active metabolite desacetylcephalothin. This metabolite was found in higher proportion in the serum (75%) than in the clots (55%). Whereas only 12% of the free (unbound) cephalothin reached the clots, 78% of the free cefamandole was found in the clots. This lower level of penetration of unbound cephalothin might be explained by the short half-life of this antibiotic, not permitting equilibrium to occur.